Nuclear contamination of water resources proceedings of the Conference Water Resource Consequences of a Nuclear Event (Thomas Telford, 1990)
In the wake of the Chernobyl disaster, the vulnerability of the water cycle to radionuclide contamination has been an issue of great concern. With contributions from eight countries, this book provides information about present radiological standards and monitoring requirements.